Loops and Building Blocks: A Knowledge co-Production Framework for Equitable Urban Health - Audia, Camilla; Berkhout, Frans; Owusu, George; Quayyum, Zahidul; Agyei-Mensah, Samuel (Springer Link, 2022)
This article was published in the Journal of Urban Health by Springer Link [Copyright © 2021, The Author(s), Provided by the Springer Nature SharedIt content-sharing initiative] and the definite version is available at: https://doi.org/10.1007/s11524-021-00531-4 The Journal's website is at: https://link.springer.com/article/10.1007/s11524-021-00531-4